Bakpia Emoticon dengan Selai Jambu Biji - Nisa Rahmaniyah Utami; Riana Dwi Putri (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2020)
Birthday celebrations are usually done by holding a party or thanksgiving. There are several things that need to be considered by parents to prepare for a child's birthday party, namely: Party Place and Decoration, Birthday Cake, Invitations, Events, Costumes, Souvenirs and Food and Drinks. Food and drinks cannot be separated from a party, because the banquet is a sign of how to appreciate the guests who attend the event. Emoticon bun is a dish that is made interesting by combining the shape of a round bun using an emoticon decoration that describes an expression. The application of emoticons in buns gives an interesting impression if the dish is specially made for children. Therefore, emoticon buns with guava jam can be used as an additional dish at a child's birthday party. The method used in this research is an experiment supported by literature studies and real work. From the results of the trial, it was obtained that emoticon bun filled with guava jam. Keywords: Birthday dish, emoticon bakpau